THE ANALYSIS OF THE INSPECTORATE AS INTERNAL AUDITOR IN REALIZING GOOD AND CLEAN GOVERNMENT IN THE POHUWATO REGENCY - Isra; Azis Rachman; Irwan Halid (Governance: Jurnal Ilmu Administrasi Publik, 2023)
The current study aims to determine the role of the inspectorate as an internal auditor. It also aims to find out the factors that hinder the role of the Internal Auditor Inspectorate in Realizing Good Governance and Clean Government in the Regional Government of Pohuwato Regency. This research uses a qualitative approach. Primary data was obtained through interviews with 8 informants within the Government Internal Supervisory Apparatus, 3 informants from related offices regarding data collection techniques. In analyzing the data, the researcher uses 3 components of activity, namely data reduction, data display, and conclusion drawing / verification. The results show that: 1) The role of the inspectorate as an internal auditor in implementing good governance in the Pohuwato District Government is in accordance with the established rules. Seen the role of a supervisor. Supervision is carried out through audit activities in identifying problems, analyzing and evaluating evidence which is carried out independently, objectively and professionally based on audit standards as well as assessing the correctness, accuracy, credibility, effectiveness, efficiency and reliability of information on the implementation of duties and functions of government agencies. 2) Factors affecting the role of the inspectorate as internal auditors in the implementation of good governance in the Pohuwato District Government are independence, quality and quantity of human resources as well as the availability of facilities and infrastructure.